Involvement of Large‐Conductance Ca2+‐Activated K+ Channels in both Nitric Oxide and Endothelium‐Derived Hyperpolarization‐Type Relaxation in Human Penile Small Arteries. (21st March 2013) - Király, István; Pataricza, János; Bajory, Zoltán; Simonsen, Ulf; Varro, András; Papp, Julius Gy.; Pajor, Lászlo; Kun, Attila
Abstract Large‐conductance Ca2+‐activated K+ channels (BKCa), located on the vascular smooth muscle, play an important role in regulation of vascular tone. In penile corpus cavernosum tissue, opening of BKCa channels leads to relaxation of corporal smooth muscle, which is essential during erection; however, there is little information on the role of BKCa channels located in penile vascular smooth muscle. This study was designed to investigate the involvement of BKCa channels in endothelium‐dependent and endothelium‐independent relaxation of human intracavernous penile arteries. In human intracavernous arteries obtained in connection with transsexual operations, change in isometric force was recorded in microvascular myographs, and endothelium‐dependent [nitric oxide (NO) and endothelium‐derived hyperpolarization (EDH)‐type] and endothelium‐independent (NO‐donor) relaxations were measured in contracted arteries. In penile small arteries contracted with phenylephrine, acetylcholine evoked NO‐ and EDH‐type relaxations, which were sensitive to iberiotoxin (IbTX), a selective blocker of BKCa channels. Iberiotoxin also inhibited relaxations induced by a NO‐donor, sodium nitroprusside. NS11021, a selective opener of BKCa channels, evoked pronounced relaxations that were inhibited in the presence of IbTX. NS13558, a BKCa‐inactive analogue of NS11021, failed to relax human penile small arteries. Our results show that BKCa channels are involved in both NO‐ and EDH‐type relaxation of intracavernous penile arteries obtained from healthy men. The effect of a selective opener of BKCa channels also suggests that direct activation of the channel may be an advantageous approach for treatment of impaired endothelium‐dependent relaxation often associated with erectile dysfunction.